Tren Riset Pendidikan Agama Islam pada Google Scholar: Sebuah Analisis Bibliometrik - Wijaya Kusumah, Mada; Meitha Kartika Herdiyanti; Farida Nur Rahma (Institut Muslim Cendekia, 2025)
This research aims to identify prominent themes (research trends) in IRE found on Google Scholar. Employing a bibliometric approach, this study utilizes databases from Google Scholar, spanning the years 2021 to 2024, to examine patterns and developments in IRE research. The research follows a five-step methodology: keyword identification (